On some features of shape perception in time deficit - Rimkutė, E. (Psichologija, 1966)
The article attempts to analyze the developmental features of contour visual image and ascertain some perceptual features when the material appears very shortly. Study variables included fixation time and object form. The results of experiment showed that the most significant change in perception appeared between the fixations with durations of 0.02 and 0.05 second. The extension of exposure time from 0.15 second did not have a greater influence of accuracy. The influence of form manifested by the fact that straight and arc-shaped lines were perceived more easily. The most mistakes were made in reproducing the parts of bent shape parts. The measuring and correcting eye-movements fail to be done on time, therefore the subject perceives the structural elements of a figure correctly, but one fails to correctly identify the in spatial terms.